2019
DOI: 10.22146/jpki.46690
|View full text |Cite
|
Sign up to set email alerts
|

Is Cadaver Still Needed in Medical Education?

Abstract: Background: Medical education has been developing very rapidly. Cadavers, which can serve as very important learning resources, need special concern for their availability and utility.Methods: This narrative review is based on related articles freely downloaded which discuss the role and availability of cadavers worldwide. The recent Indonesian condition with Universitas Gadjah Mada as a case will be described.Results: Cadavers play important roles in several aspects, from bioethics and behavioral development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
4
0
4
Order By: Relevance
“…Hal tersebut menyebabkan kebutuhan media pembelajaran lain sebagai pengganti atau pelengkap pembelajaran anatomi dengan modalitas kadaver. 7 Beberapa metode pembelajaran anatomi selain diseksi kadaver, yakni aplikasi anatomi tiga dimensi (3D) berbasis komputer termasuk penggunaan gawai meja visualisasi anatomi mulai direkomendasikan. 1,2 Meja visualisasi anatomi dinilai mampu menghadirkan hubungan spasial lebih baik dibandingkan metode lain di luar diseksi atau proseksi kadaver, misalnya buku teks atau aplikasi anatomi dua dimensi (2D) berbasis komputer.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Hal tersebut menyebabkan kebutuhan media pembelajaran lain sebagai pengganti atau pelengkap pembelajaran anatomi dengan modalitas kadaver. 7 Beberapa metode pembelajaran anatomi selain diseksi kadaver, yakni aplikasi anatomi tiga dimensi (3D) berbasis komputer termasuk penggunaan gawai meja visualisasi anatomi mulai direkomendasikan. 1,2 Meja visualisasi anatomi dinilai mampu menghadirkan hubungan spasial lebih baik dibandingkan metode lain di luar diseksi atau proseksi kadaver, misalnya buku teks atau aplikasi anatomi dua dimensi (2D) berbasis komputer.…”
Section: Pendahuluanunclassified
“…Kedua modalitas ini akan saling melengkapi kekurangan masing-masing dalam menunjang pembelajaran anatomi. [6][7][8][9][10] Selain itu, kemampuan visual-spasial mempunyai andil dalam pembelajaran AVL.…”
Section: Hasil Dan Pembahasanunclassified
“…Anatomy is one of the main subjects in the health and medicine field that is important to understand the structure of the human body (1,2). For many students, anatomy is a difficult subject because the human body consists of a group of complex organs with detailed structures and specific names (3).…”
Section: Introductionmentioning
confidence: 99%
“…A Cadaver is a preserved dead human body, which is often used for anatomy learning in the fields of medicine 1 . From the renaissance period until the 21 st century, embalmed cadavers were used for dissection and learning, and have not been fully replaced with the interactive multimedia method until now [2][3][4][5] . Compared to artificial anatomical figures, they show a keen precision of anatomical structure and complexity, which portray the anatomy of living humans.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, touching and palpating preserved cadavers by medical students provide a better three-dimensional picture of the body. Students also agreed that learning with this method helps them to understand anatomy completely [5][6][7] . Previous studies revealed that preserved cadavers using typical embalming formulas, such as formalin show a different color, consistency, and organ volume compared to living humans 8,9 .…”
Section: Introductionmentioning
confidence: 99%